The influence of corporate social responsibility of the organization towards increasing sales and loyalty of hotel services in Bangkok (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to investigate demographic factors, compare the importance and relationship of levels of organizational corporate social responsibility (CSR) towards increasing sales and loyalty of hotel services in Bangkok. The population in the study was persons who use and experienced using hotel services in Bangkok. The sample comprised 400 persons. The findings from the study revealed that gender, age, levels of education, and career differences did not have an effect on increasing sales and brand loyalty with the statistical significance level of 0.05 but marital status and monthly income had an effect on increasing sales and brand loyalty with the statistical significance level of 0.05. Moreover, the study result indicated that corporate social responsibility of the organization, as a whole, was at a high level of importance classified by the top 3 rank orders, namely, responsibility to consumers, environment care, business operation, and organizational justice were related to increasing sales and brand loyalty in the same direction with statistical significance level of 0.01.